Attachment of the chromosomal terminus of Bacillus subtilis to a fast-sedimenting particle. - Sargent, M G (1982)
After gently lysed protoplasts of exponential phase cells of Bacillus subtilis were treated with restriction endonuclease BamHI, 99% of the DNA did not sediment with the plasma membrane. This DNA was fractionated on sucrose gradients into (i) a fast-sedimenting fraction highly enriched for genes from the origin and terminus (purA and ilvA), (ii) a 50 to 100S component also enriched for purA and ilvA, and (iii) the bulk of the DNA. The fast-sedimenting fraction was dissociated by Sarkosyl; this fraction contained a substantial amount of protein and is probably a membrane subparticle. The S value of the 50 to 100S component was not greatly affected by Sarkosyl treatment, but these particles were unable to penetrate an agarose gel during electrophoresis and were retained by nitrocellulose filters. The terminus DNA in the fast-sedimenting fraction and the 50 to 100S component contained a large restriction fragment (1.5 x 10(7) to 2.0 x 10(7) daltons) encoding ilvA, thyB, and ilvD. The bulk of the SP beta prophage and metB, which lie to the right and left, respectively, of the ilvA-ilvD cluster, were not part of the complex. citK, which lies to the right of SP beta, appeared to be present in the fast-sedimenting complexes. The neighboring genes kauA and gltA were not part of the fast-sedimenting complexes. The presence of terminus DNA in the fast-sedimenting components was also demonstrated by a radiochemical method.